Global Halal Fashion Industry: Predictions and Developments - Mahendra, Ikhsan Fitrah; Nurkamal, Farras; Rabbani, Muhamad Farhan (SMART Insight, 2025)
The halal fashion industry is one of the main subsectors in the global halal economy that shows significant growth along with the increasing Muslim population of the world, awareness of the halal lifestyle, and the development of creative industries based on sharia values. This study aims to predict the development of the market size of the global halal fashion industry using a time series quantitative approach. The data used is sourced from the Global Islamic Economics Report (GIER) for the period 2012–2017. The forecasting methods used include Trend Analysis, Multiplicative Decomposition, and Exponential Smoothing with Trend, with the help of POM-QM software version 3. The results of the study show that the global halal fashion industry is predicted to continue to grow in the medium term, with an estimated market value in 2019 in the range of USD 274–279 billion. Based on the Mean Absolute Percentage Error (MAPE) value, the Trend Analysis and Multiplicative Decomposition methods show a relatively better level of accuracy than Exponential Smoothing with Trend. These findings affirm the positive outlook of the global halal fashion industry and the importance of using the right forecasting methods as the basis for the formulation of business strategies and policies for the halal industry.